Reconciling the Divergence in Aggregate U.S. Wage Series - Julien Champagne; Andre Kurmann; Jay Stewart (Institute for the Study of Labor (IZA), 2016)
According to data from the Labor Productivity and Costs (LPC) program, average hourly real compensation in the United States has grown consistently over time and become markedly more volatile since the mid-1980s. By contrast, data from the Current Employment Statistics (CES) imply that average hourly real earnings has mostly stagnated and become substantially less volatile. We show that differences in earnings concept and differences in worker coverage account for the majority of this divergence in growth and volatility. The results have important implications for the appropriate choice of aggregate wage series for macroeconomic analysis.
Keywords: E01; E24; E30; J30; 330; comparison of hourly earnings data; earnings trends; earnings volatility